Anlotinib induced type 1 diabetes: a case report - Chen, Jing; Xia, Daohan; Ke, Linqiu (Frontiers in Oncology, 2025)
Studies have shown some tyrosine kinase inhibitors (TKIs) can influence glucose metabolism leading to either hypoglycemia or hyperglycemia which is reversable in most patients after treatment cessation. Anlotinib is a novel oral multi-target tyrosine kinase inhibitor (TKI) which has been approved for non-small cell lung cancer in China. Previous studies of anlotinib did not report it has any side effect on blood glucose, and there has been no case reporting type 1 diabetes associated with any TKI. The present case study, to our knowledge, was the first to report on an 81-year-old man with lung cancer who developed type 1 diabetes following 14 cycles treatment with TKI. The fasting plasma blood glucose and hemoglobinA1c (HbA1c) was 24.3mmol/L and 9.0%, respectively, and GADA (glutamic acid decarboxylase antibody) was more than 2000IU/ml (normal range is less than 10IU/ml) when he was diagnosed. We also conducted a literature review to explore the potential mechanism of anlotinib in inducing type 1 diabetes and recommend that self-monitoring blood glucose (SMBG) for fasting and random postprandial blood glucose at least once a week is needed for early identification of glucose dysregulation when using TKI drugs, and monthly fasting and random postprandial plasma glucose monitoring and HbA1c test every 3 months is also recommended if the SMBG protocol cannot be completed.